P-135 Deconditioning, the hidden menace, in the palliative care patient. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Campbell, Amanda; Kidsley, Karen; Hooper, Alison; Magee, Marie
Abstract : Background: Deconditioning can masquerade as general fatigue and disease progression, impacting function, confidence, reducing independence and quality of life, increasing the need for adaptions and care. It is a hidden menace. Deconditioning can be reversed with achievable focused strengthening exercises; this is good news for the palliative care patient. Aims: To enable identification and management of deconditioning in palliative care patients. To improve outcomes for deconditioned palliative care patients. Method: Create a screening process and exercise programmes for healthcare professionals to identify and advise individuals. Provide internal and external training for professionals. Provide online resources for professionals and patients. Provide weekly 'pop-up gym' sessions within the hospice for patients to receive individually prescribed exercise programmes. Provide regular talks for patients within the Sunflower Centre, highlighting the importance of exercise and the risks associated with deconditioning. Results: Deconditioning screening tools, each with decision-making guide and subsequent exercise programme created (2015). Deconditioning training workshops for professionals (2015), extended to external providers (2017). Word documents created (2015), with online resources of video clips (2016), supporting patients and professionals. Patient resources both generic and individually prescribed according to need. Patients have regained independence within short weeks using the advice and exercise. Healthcare professionals have replicated these results following the training. Positive patient feedback has been received: ' the greatest benefits are it has given me the strength and belief in myself' ' feeling strong enough to pursue further treatment options ' ' Improved my quality of life… be more positive… enjoy life as much as possible. ' Gym sessions and talks began (2018) within the Sunflower Centre. Nine patients participated with personalised outcome measures identifying the programme benefits. Conclusion: Results indicate positive qualitative feedback and increased professional awareness. Progression requires quantitative data, increased signposting for recognition and prevention, along with professional practice support in identification and advice.